2018
DOI: 10.4049/jimmunol.1701010
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Plasmodium falciparum Induces Trained Innate Immunity

Abstract: Malarial infection in naive individuals induces a robust innate immune response. In the recently described model of innate immune memory, an initial stimulus primes the innate immune system to either hyperrespond (termed training) or hyporespond (tolerance) to subsequent immune challenge. Previous work in both mice and humans demonstrated that infection with malaria can both serve as a priming stimulus and promote tolerance to subsequent infection. In this study, we demonstrate that initial stimulation with -i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 31 publications
7
118
6
Order By: Relevance
“…In a recently reported phase 1 clinical study, BCG-vaccinated individuals given a dose of P. falciparum were shown to afford better control of malaria, concomitant with early activation of granzyme B + NK cells and HLA-DR + monocytes (Walk et al, 2019). Non-vaccinated controls did not show similar results, suggesting that BCG-driven innate immune activation leads to cross-protection against a protozoan parasite, in keeping with a previous finding describing pro-inflammatory, adherent innate immune cells responses due to plasmodium-triggered, trained immune responses (Schrum et al, 2018). In another study, Arts et al (2018b) reported that BCG vaccination would induce a genome-wide epigenetic reprograming of monocytes.…”
Section: Can Trained Immunity Be Exploited For Therapeutic Purposes?supporting
confidence: 74%
See 1 more Smart Citation
“…In a recently reported phase 1 clinical study, BCG-vaccinated individuals given a dose of P. falciparum were shown to afford better control of malaria, concomitant with early activation of granzyme B + NK cells and HLA-DR + monocytes (Walk et al, 2019). Non-vaccinated controls did not show similar results, suggesting that BCG-driven innate immune activation leads to cross-protection against a protozoan parasite, in keeping with a previous finding describing pro-inflammatory, adherent innate immune cells responses due to plasmodium-triggered, trained immune responses (Schrum et al, 2018). In another study, Arts et al (2018b) reported that BCG vaccination would induce a genome-wide epigenetic reprograming of monocytes.…”
Section: Can Trained Immunity Be Exploited For Therapeutic Purposes?supporting
confidence: 74%
“…There is also evidence of Plasmodium falciparum (Pf )-induced trained immunity in adherent cells from peripheral blood mononuclear cells (PBMCs) -most likely macrophages -which undergo H3K4 trimethylation leading to their subsequent ability to produce high amounts of IL-6 an TNF-α in response to TLR1/2 stimulation with Pam3CSK4 in a manner dependent on hemozoin or Pf -infected erythrocytes (Schrum et al, 2018). TLR1 and 2 recognize peptidoglycan, a quintessential component of the bacterial cell wall, and can engage NF-κB activation for pro-inflammatory cytokine signaling, as shown in the context of antimycobacterial immune responses (Takeuchi et al, 2002).…”
Section: Macrophages and Dendritic Cellsmentioning
confidence: 99%
“…This concept emerged from observations that innate immunity can be crucial for re-infections [66] . Indeed, trained immunity involves epigenetic and metabolic reprogramming of innate immune cells [66] and is induced by P. falciparum infection [67] . Our data suggest that metabolic reprogramming of myeloid cells could have a substantial effect on the development of clinical tolerance to re-infection with P. vivax , in which platelets play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to adaptive T cell memory, innate-like memory in γδ T cells is an intriguing alternative supported by evidence that monocytes can adapt secondary response to infection based on priming-induced epigenetic reprogramming ( 106 , 107 ). A recent study has observed this phenomenon, termed “trained immunity”, in monocytes stimulated in vitro with Pf -iRBCs or from children living in malaria-endemic regions ( 108 ). Preliminary evidence showing epigenetic reprogramming at the PD1 locus in neonatal Vγ9Vδ2 cells ( 36 ) suggests that a similar process could be responsible for the immunoregulatory phenotype seemingly acquired among γδ T cells after multiple infections ( 34 , 39 ).…”
Section: Potential For Immunological Memory In Malaria-responsive γδmentioning
confidence: 97%